Search for heavy quarks decaying into a top quark and a W or Z boson using lepton + jets events in pp collisions at √s = 7 TeV - Chatrchyan, S. (2013)
Results are presented from a search for the pair-production of heavy quarks, QQ̄, that decay exclusively into a top quark and a W or Z boson. The search is performed using a sample of proton-proton collisions at √s = 7 TeV corresponding to an integrated luminosity of 5.0 fb-1, collected by the Compact Muon Solenoid experiment. The signal region is defined using a sample of events containing one electron or muon, missing transverse momentum, and at least four jets with large transverse momenta, where one jet is likely to originate from the decay of a bottom quark. No significant excess of events is observed with respect to the standard model expectations. Assuming a strong pair-production mechanism, quark masses below 675 (625) GeV decaying into tW (tZ) are excluded at the 95 % confidence level.[Figure not available: see fulltext.] © 2013 CERN for the benefit of the CMS collaboration.